Genetic analysis of nitrogen accumulation and protein composition in wheat kernel - Charmet G.; Martre P. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The maximum rate and duration for grain dry matter (DM) and nitrogen (N) accumulation were evaluated for 194 recombinant inbred lines (RILs) from a cross between two French wheat cultivars. Grain protein composition was analysed by capillary electrophoresis (CE) and size-exclusion high performance liquid chromatography (SE-HPLC). Correlation analyses revealed that DM and N accumulation rates were closely related, and that protein composition was primarily influenced by the total quantity of N per grain. A genetic map of 254 molecular markers allowed us to identify 7 quantitative trait loci (QTL). Five QTLs were significantly associated with the kinetics of DM and N accumulation, and two of them also influenced protein composition. Two QTLs affected only the protein composition. We also used the SiriusQuality1 wheat simulation model to analyze genotype × environment interactions for grain protein composition. QTLs for the genotypic key parameters of total grain nitrogen partitioning were detected.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)